Improvement of oxygen-uptake kinetics and cycling performance with combined prior exercise and fast start - Brock, K.; Antonellis, P.; Black, M. I.; DiMenna, F. J.; Vanhatalo, A.; Jones, A. M.; Bailey, S. J. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate whether oxygen-uptake (VO2) kinetics and simulated 4-km cycling performance are synergistically improved by prior "priming" exercise and an all-out starting strategy. Methods: Nine men completed 4 target work trials (114±17 kJ) to assess VO2 kinetics and cycling performance in a repeated-measures, crossover experimental design. Trials were initiated with either a 12-s all-out start or a self-selected start and preceded by prior severe-intensity (70%) priming exercise or no priming exercise. Results: The VO2 mean response time (MRT) was lower (indicative of faster VO2 kinetics) in the all-out primed condition (20±6 s) than in the all-out unprimed (23±6 s), self-paced-unprimed (42±13 s), and self-paced-primed (42±11 s) trials (P<.05), with the VO2 MRT also lower in the all-out unprimed than the self-paced unprimed and self-paced primed trials (P<.05). Trial-completion time was shorter (performance was enhanced) in the all-out primed trial (402±14 s) than in the all-out unprimed (408±14 s), self-paced unprimed (411±16 s), and self-paced primed (411±19 s) trials (P<.05), with no differences between the latter 3 trials. Conclusions: The findings from this study suggest that combining severe-intensity priming exercise with a short-duration all-out starting strategy can expedite the adjustment of VO2 and lower completion time during a cycling performance trial to a greater extent than either intervention administered independently. These results might have implications for optimizing performance in short-duration high-intensity competitive events such as a 4-km cycling time trial.